A clinical phase I study of an EB66 cell-derived H5N1 pandemic vaccine adjuvanted with AS03. Issue 45 (9th November 2015) - Naruse, Takeshi; Fukuda, Tadashi; Tanabe, Tetsuro; Ichikawa, Munetaka; Oda, Yoshiaki; Tochihara, Shinji; Kimachi, Kazuhiko; Kino, Yoichiro; Ueda, Kohji
Abstract: Background: We conducted a phase I clinical trial of a cell culture-derived AS03-adjuvanted influenza vaccine containing HA antigen (A/Indonesia/05/2005(H5N1)/PR8-IBCDC-RG2) derived from EB66 cells (KD-295). Methods: Healthy male adult volunteers (20–40 years old, N  = 60) enrolled in the study were divided into 3 groups, the MA group (3.8 μg of HA + AS03), HA group (7.5 μg of HA + AS03), and 1/2 MA group (half the volume of the MA group), and received KD-295 intramuscularly twice with a 21-day interval. After administration of KD-295, adverse events, clinical laboratory parameters, and immune response to the vaccine strain and heterologous virus strains were evaluated. Results: No severe adverse events leading to discontinuation of vaccine administration occurred. The vaccine was well-tolerated. There was no dose dependency in the rate, timing, or duration of the adverse events. Immunogenicity of the vaccines was evaluated by HI (hemagglutination inhibition) assay, which confirmed that the antibody response to the vaccine strain and heterologous strain in all groups met the three criteria for immunogenicity described in the Japanese guidelines for development of a pandemic prototype vaccine. We also measured the neutralizing antibody titers against several virus strains, and confirmed a significant rise in antibody levels to both the vaccine strain and heterologous strains. Conclusion: The EB66-derived H5N1 influenza vaccine adjuvanted with AS03 elicited a broad cross-reactive antibody response among H5N1 strains with acceptable reactogenicity. Therefore, KD-295 can be considered a useful pandemic and pre-pandemic influenza vaccine candidate.